1978
DOI: 10.54302/mausam.v29i1.2862
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations of monsoon activity

Abstract: In order to study the evolution of flow patterns associated with 'strong' and 'break' monsoon we have studied six cases each of such epochs during the period 1965 to 1973. As we are interested in the departure of the flow patterns from the normal, we have subtracted long term climatological pentad means from the daily data and constructed anomaly wind, height and thickness charts at standard levels. The several contrasting features during the epochs as well as prior to the epochs. A few  days prior to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…MISOs are the periodic oscillation of dry (break) and wet (active) spells of precipitation which have a time scale longer than diurnal and synoptic variability but shorter than a season. Earlier studies (ALEXANDER et al 1978;Yasunari 1980; Goswami and Ajaya Mohan 2001) have shown that MISOs have a preferred scale of periodicity between 20 to 90 days. A repeated northward movement of cloud bands from south of the equator to the foothills of the Himalayas is associated with active and break spells of monsoon (Yasunari 1979; Sikka and Gadgil 1980; Krishnamurti and Subrahmanyam 1982).…”
Section: Introductionmentioning
confidence: 95%
“…MISOs are the periodic oscillation of dry (break) and wet (active) spells of precipitation which have a time scale longer than diurnal and synoptic variability but shorter than a season. Earlier studies (ALEXANDER et al 1978;Yasunari 1980; Goswami and Ajaya Mohan 2001) have shown that MISOs have a preferred scale of periodicity between 20 to 90 days. A repeated northward movement of cloud bands from south of the equator to the foothills of the Himalayas is associated with active and break spells of monsoon (Yasunari 1979; Sikka and Gadgil 1980; Krishnamurti and Subrahmanyam 1982).…”
Section: Introductionmentioning
confidence: 95%
“…Additionally, break monsoon conditions, when the monsoon trough lies close to the foothills of the Himalayas, are extremely conducive for rainfall in NEI (Rahecha & Pisharoty, 1996; Ramamurthy, 1969; Rao, 1976). Several studies have provided extensive documentation of the active and break monsoon conditions in terms of intraseasonal oscillations (ISO) (Alexander et al, 1978; Goswami & Ajayamohan, 2001; Krishnamurthy & Shukla, 2007, 2008; Krishnamurti & Bhalme, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Such years with below-normal rainfall are termed by Asian meteorologists as 'drought years' or 'bad monsoon' years. The anomalies for drought situation over Indian region were studied extensively by a number of workers (Ramamurty 1969;Joseph 1978;Alexander et al 1978). The main observations for drought situation are that (i) the rainfall is well below normal or completely absent over north Indian plains region, (ii) the surface pressure shows a positive anomaly of.…”
Section: Introductionmentioning
confidence: 99%